AI CHATBOTS IN EFL: SYNTHESIZING COGNITIVE, PSYCHOLOGICAL, AND ETHICAL IMPLICATIONS - Syaifulloh, Rizal Bagus; Yappi, Shierly Novalita (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The integration of AI-powered chatbots into English as a Foreign Language (EFL) education has garnered increasing attention for its potential to enhance language learning outcomes. This study presents a systematic review of 43 peer-reviewed articles published between 2023 and 2025, aiming to synthesize current evidence on the cognitive, psychological, and ethical implications of chatbot use in EFL contexts. The findings are thematically categorized into three domains: (1) cognitive outcomes, including improvements in vocabulary acquisition, grammar mastery, and writing fluency; (2) psychological impact, such as increased learner confidence and reduced language anxiety; and (3) ethical concerns, particularly related to data privacy, algorithmic bias, and digital equity. While the overall impact of chatbots is positive, several studies caution against over-reliance on AI tools and highlight the need for more transparent and ethically grounded implementations. This review concludes that AI chatbots can serve as effective supplemental tools in EFL learning when integrated thoughtfully and ethically. The study offers practical recommendations for educators and proposes future research directions to address current gaps in evidence, particularly regarding long-term impact and ethical safeguards. ABSTRAKIntegrasi chatbot berbasis kecerdasan buatan (AI) dalam pembelajaran Bahasa Inggris sebagai Bahasa Asing (EFL) semakin mendapat perhatian karena potensinya dalam meningkatkan hasil belajar bahasa. Studi ini menyajikan tinjauan sistematis terhadap 43 artikel ilmiah terbitan tahun 2023 hingga 2025 untuk mensintesis bukti terkini mengenai implikasi kognitif, psikologis, dan etis dari penggunaan chatbot dalam konteks EFL. Temuan dikategorikan ke dalam tiga domain tematik: (1) hasil kognitif, meliputi peningkatan penguasaan kosakata, tata bahasa, dan kelancaran menulis; (2) dampak psikologis, seperti peningkatan kepercayaan diri dan penurunan kecemasan berbahasa; serta (3) isu etis, khususnya terkait privasi data, bias algoritmik, dan kesenjangan digital. Meskipun dampak penggunaan chatbot secara umum bersifat positif, beberapa studi memperingatkan potensi ketergantungan berlebihan terhadap alat AI dan menyoroti perlunya penerapan yang transparan dan berlandaskan etika. Kajian ini menyimpulkan bahwa chatbot AI dapat berperan sebagai alat bantu pembelajaran yang efektif dalam konteks EFL jika diintegrasikan secara bijak dan etis. Studi ini juga menawarkan rekomendasi praktis bagi para pendidik serta mengusulkan arah penelitian lanjutan untuk menjawab kesenjangan bukti, khususnya terkait dampak jangka panjang dan perlindungan etis.